Penerapan Aplikasi Augmented Reality pada Alat Keselamatan Berkendara Bermotor - Tamba, Alfred; Zakariyah, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Augmented reality is a technology that combines two dimensions into the real world into 3D objects. Augmented reality has been widely used in various sector, especially in the sector of safety. Augmented reality can be used as an information aid. In making this augmented reality, the software needed is Unity, Vuforia SDK, and Figma. The implementation of motorized driving safety in Indonesia is still lacking; therefore, an application is needed that can help motorists choose safe driving using augmented reality. With the application of augmented reality to motorcycle driving safety, it is hoped that it can educate the public about safety when driving to reduce injuries and fatalities.